2005
DOI: 10.1007/s10450-005-4901-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibrium of Alkanes on a High Surface Area Activated Carbon Prepared from Brazilian Coconut Shells

Abstract: Adsorption equilibria of methane, ethane, and n-butane on a high surface area activated carbon prepared from Brazilian coconut shells is examined in this study. The material shows high capacities for the alkanes tested. A group-contribution theory is used to predict adsorption isotherms for all three components with very good accuracy employing one set of model parameters. The theory is also used to observe trends in isosteric heat of adsorption as a function of loading at various temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Temperature dependency is also built into this model. Therefore, the parameters given for alkanes adsorption on BPL carbon (Walton et al, 2004) and coconut shell carbon (Walton et al, 2005) are applicable to the entire operating range considered here. Pure-component isotherms and model predictions for methane, ethane, and n-butane on both BPL and BCA carbon at 298 K are shown in Figure 2.…”
Section: Multicomponent Adsorption Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Temperature dependency is also built into this model. Therefore, the parameters given for alkanes adsorption on BPL carbon (Walton et al, 2004) and coconut shell carbon (Walton et al, 2005) are applicable to the entire operating range considered here. Pure-component isotherms and model predictions for methane, ethane, and n-butane on both BPL and BCA carbon at 298 K are shown in Figure 2.…”
Section: Multicomponent Adsorption Modelmentioning
confidence: 98%
“…Pure-component isotherms and model predictions for methane, ethane, and n-butane on both BPL and BCA carbon at 298 K are shown in Figure 2. Isotherms for these and other components and mixtures at different temperatures are given elsewhere (Walton et al, 2004(Walton et al, , 2005. BCA carbon has higher capacities for butane than BPL carbon.…”
Section: Multicomponent Adsorption Modelmentioning
confidence: 99%
“…Some studies have suggested that methane adsorbed to organic materials can be released into methanefree air at steady rates for periods of days to weeks (Zhang and Krooss, 2001;Cheng and Huang, 2004). Unfortunately, few data are available for low-pressure methane adsorption capacities of non-activated compounds, and extrapolation from available adsorption isotherms to a low pressure range is limited due to the very strong pressure-dependence of adsorption at low pressures (Shao et al, 2004;Walton et al, 2005;Garcia-Perez et al, 2007;Saha et al, 2007). Kirschbaum et al (2007) estimated an adsorption potential of about 40 000 ngCH 4 kgDW −1 based on the adsorption characteristics of plant cell walls of coconut charcoal when they assumed a simple linear dependence of adsorption on methane partial pressure.…”
Section: Reported a New Finding Thatmentioning
confidence: 99%
“…The adsorption of natural gas in porous materials, in which case the gas may be stored (ANG) under moderate pressures (between 3.5 and 4.0 MPa), has been studied as an alternative for its storage and transport (Parkyns et al 1995;Sun et al 1996;Lozano-Castelló et al 2002a, 2002bAzevedo et al 2007;Bastos-Neto et al 2005;Walton et al 2005;Zhang et al 2008;Prauchner and Rodriguez-Reinoso 2008). According to Cook et al (1999), activated carbon (AC) is the most adequate material for NG storage systems due to its textural properties-such as surface area and micropore volume-which may be tailored according to a given adsorbate, besides being hydrophobic and having high affinity for organic substances.…”
Section: Introductionmentioning
confidence: 99%